Has the Sun Set on Quantum Dot- Sensitized Solar Cells? - Toshia L. Wrenn; James R. McBride; Nathanael J. Smith; Sandra J. Rosenthal (Nanomaterials and Nanotechnology)
A reminder, a review and a look toward the future pros‐ pects for quantum dot-sensitized solar cells — a reminder of the highly viable, energy-efficient solar cells achievable; a review of ground-breaking devices and their similarities to the near unity photon-to-electron mechanisms of photosynthesis; a look toward architectures that capitalize on the advances observed in previous work.